DESTABILIZATION OF THE MANIPUR STATE AND THE ROLE OF MYANMAR REFUGEES BEHIND THE ARTIFICIALLY ENGINEERED VIOLENCE - Ningthilsana, Chingangbam; Shukla, Arvind Shanker (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The destabilization of Manipur is because of breaking the Suspension of Operation ground rules by Kuki’s militants that was signed between the central, state, and Kuki’s groups in 2008. The sudden increase in Kuki’s Population happens after this agreement by bringing huge illegal immigrants from Myanmar to Manipur, India. Building a huge population, using them for poppy cultivation, engaging in drugs and arms trafficking, making huge demographic changes in the Manipur state, and posing a threat to the indigenous people. Manipur is very close to the Golden Triangle and it has an ancient gateway to the Southeast Asian nations through Moreh town. This paper is based on primary data and used secondary data from local papers and journals. The state government is afraid that some hill parts of the state may fall under this region. Districts like Churchandpur, Tengnoupal, Kamjong, and Ukhrul have practiced the highest poppy cultivation followed by other hill districts. The central government decided to start border fencing to stop illegal infiltration and terminate the Free Movement Regime (FMR) which allows both citizens to enter up to 16 km without any proper document but was opposed by other north-eastern states due to its own interest. Temporary refugee camps are set up in the hill districts of Manipur.